2011
DOI: 10.1007/s00024-011-0354-7
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Rupture at Focal Depth, Part I: Structure and Rupture of the Pretorius Fault, TauTona Mine, South Africa

Abstract: We analyze the structure of the Archaean Pretorius fault in TauTona mine, South Africa, as well as the rupture-zone that recently reactivated it. The analysis is part of the Natural Earthquake Laboratory in South African Mines (NELSAM) project that utilizes the access to 3.6 km depth provided by the mining operations. The Pretorius fault is a *10 km long, oblique-strikeslip fault with displacement of up to 200 m that crosscuts fine to very coarse grain quartzitic rocks in TauTona mine. We identify here three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 44 publications
(56 reference statements)
3
22
0
Order By: Relevance
“…Such mechanisms are expected from the results of Lucier et al . [] on normal faulting stress conditions in the nearby TauTona mine, and that faults dipping 50°–85° to the east‐northeast or west‐southwest are critically stressed based on the Coulomb failure criterion [ Heesakkers et al ., , ]. Faults with such parameters are also supported by direct in situ observations at the exploitation level [ McGarr , , ; Cichowicz et al ., ; van Aswegen , 2008].…”
Section: Analysis Resultsmentioning
confidence: 72%
“…Such mechanisms are expected from the results of Lucier et al . [] on normal faulting stress conditions in the nearby TauTona mine, and that faults dipping 50°–85° to the east‐northeast or west‐southwest are critically stressed based on the Coulomb failure criterion [ Heesakkers et al ., , ]. Faults with such parameters are also supported by direct in situ observations at the exploitation level [ McGarr , , ; Cichowicz et al ., ; van Aswegen , 2008].…”
Section: Analysis Resultsmentioning
confidence: 72%
“…TauTona`s gold deposits are currently mined at depths of 2-3.5 km, and shafts are under construction to extend mining to below 4 km. The shafts cross through the about 10 m wide and about 10 km long Pretorius Fault Zone (PFZ), the largest fault in the western deep area of the mine (Heesakkers et al, 2011a;Heesakkers et al, 2011b). Figure 1 illustrates the location of an approximately 25 m 2 cubby that was excavated particularly for the purpose of the DAFSAM-NELSAM earthquake laboratory (Reches, 2006) directly within the PFZ at 3.54 km depth.…”
Section: Introductionmentioning
confidence: 99%
“…Deep mines, where many earthquakes are induced by the stress concentration produced by excavation, provide a good opportunity to deploy an observation network that can detect very small earthquakes. However, even in observations in mines, there are no published examples of a preexisting fault that was clearly delineated by steady activity of microseismic events, though some studies reported that a larger earthquake (M N~2) reactivated part of a geological fault (e.g., Heesakkers et al, 2011). For example, Snelling et al (2013) investigated hypocenter distributions of -2.3 ≤ M W ≤ 0.8 events and reported that there was no correlation between the hypocenters and geological faults near the microseismic network.…”
Section: Introductionmentioning
confidence: 93%